Evaluating the effect of the temporomandibular disorder treatment over tinnitus - Webster, Guilherme; Ikino, Cláudio Márcio Yudi; Salles, Bertholdo Werner; Lino, Aline da Rocha; Manoel, Evandro Maccarini; Filho, Waldir Carreirão (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The interaction between tinnitus and temporomandibular disorders is a very complex issue that has been long approached, because neither the etiologic factors nor the pathogenesis of such a two-way association has been clearly defined yet. Additionally, tinnitus is known to be more prevalent in temporomandibular dysfunction individuals in comparison with the general population, hence, suggesting the existence of this two-way association.Objective: Evaluate the effect of the temporomandibular disorder treatment when tinnitus is noticed.Methods: It is about a prospective cohort study, in which temporomandibular dysfunction (TMD) individuals showing a tinnitus before and after the dental TMD treatment were studied. Patients' age, sex, and tinnitus features - place of symptom and time length were examined, and an audiometric evaluation was performed. Intensity of tinnitus was evaluated by a digital analogue scale before and after the TMD treatment.Results: We evaluated 15 TMD and tinnitus patients aged between 37.7 ±  17.1, 86.7% of whom were female. In 60% of the cases, tinnitus was unilateral and the average time length was 24 months. In 5 (33.3%) patients, a neurosensorial hearing loss was seen at audiometry. When comparing the visual analogue scale scores before and after the dental treatment, a significant decrease (p < 0,001) in the intensity of tinnitus was evident. In 4 (26.6%) patients, tinnitus disappeared.Conclusion: A significant decrease in the recognition of tinnitus by patients submitted to a temporomandibular dysfunction treatment was evident.
Keywords: hearing disorder; tinnitus; temporomandibular joint dysfunction; craniomandibular disorders